A philosophical examination of the concept and nature of suicide as a socio-ethical issue - Amaobi Nelson Osuala (Center for Humanities and Innovation Studies, 2019)
This paper critically examines the nature of suicide as a contemporary Socio-ethical issue. It argues that the phenomenon of suicide is one that can be understood from varied standpoints, especially where it refers to the reasons why most people contemplate suicide. In this paper, I tried to show those moments in which the notion of suicide seems to project ambivalence based on some foundational ethical principles, some of which seem to justify or condemn the act of suicide. Some of the arguments thus examined include amongst others, the theological argument, domino argument, legal principles, justice argument, and utilitarian principle etcetera. It was against this backdrop that I took a bent and reached a crescendo in which case I maintained that the notion of suicide runs contrary to the fundamental ethical value of traditional Igbo aborigines of the complementary system of thought, the latter who avers that ndu bu isi (life is of supreme value). It was upon this premise as well as other principles of human co-existential experience that I condemned the act of suicide. I employed the philosophical tools of skeptic-critical evaluation cum analysis to arrive at this conclusive conclusion.